Peningkatan Kinerja Pemasaran Syariah melalui Kemampuan Inovasi Produk - Muhammad Akmal; Alifah Ratnawati (Universitas Muhammadiyah Surabaya, 2022)
AbstractThis study aims to determine the role of product innovation ability and the improvement of sharia marketing performance. The ability of product innovation refers to the influence factors. It is a process that emphasizes achieving and creating unique and interesting new things. As well as using the process to build the ability to innovate within a company or organization. It is based on a view based on the individuals or groups subjectivity becoming the focal point and the main factor in the innovation process of a company or organization. The ability of product innovation must ensure that the process of creating new things is created continuously. Specifically in an effort to improve the Sharia marketing performance that will be achieved, especially for those who have many competitors or those who are prone to saturation. The paradigm in the importance of the innovation ability must be an encouragement for the progress in a business, its systems and arrangements. The ability of product innovation affects the Sharia marketing performance which is implemented by the company then affects the economic development. This will be an enrichment source for organizations in strengthening Shariah marketing performance. Keywords: Sharia marketing performance, Product Innovation Ability, Innovation Ability Factors